Os saltos do “canguru” nos canaviais alagoanos. Um estudo sobre trabalho e saúde - Verçoza, Lúcio Vasconcellos de (2016)
This thesis aims to study the working conditions in the sugarcane agribusiness in Alagoas and its effects on workers' health. The issue studied was the analysis of working conditions and health in the face the current situation of sugarcane agribusiness in Alagoas: characterized by productive restructuring and the intensification of work in manual cutting of sugarcane. The increased effort required in this labor activity produces besides the physical, moral and psychological distress. . This thesis is justified to the extent that it aims to complete at least two gaps with regard to health approach to rural workers: the absence of research focusing on the physical health of workers articulated the moral and psychological distress; and the absence of studies on the cane fields of Alagoas that communicate substantially with the research undertaken in the cane fields of Sao Paulo. The main objective of this research was to contribute to the reflections on the causal connection between illness and the cane cutting job. To achieve this scope, field research and interviews were carried out with cane cutters, mill former residents, unemployed because of illness, cable (surpervisor), plant manager, medical, among other key informants; furthermore it was performed exercise testing, monitoring heart rate during labor, application Nordic Musculoskeletal Questionnaire and physical evaluation - procedures performed with the collaboration of doctors and fitness trainers -. The interviews were conducted by the methodology of oral history. The municipality of Teotonio Vilela was the privileged empirical universe by concentrating a large number of workers employed in various plants in the south of Alagoas. The data collected indicate existence of direct relationship between work in the cane fields and the early exhaustion of physical and spiritual energies of workers.